Presence of Brucella spp. in Milk and Dairy Products: A Comprehensive Review and Its Perspectives - Md. Sadequl Islam; Md. Ariful Islam; Md. Moshiur Rahman; Khaleda Islam; Md. Mominul Islam; Md. Murtuza Kamal; Md. Nazrul Islam (Journal of Food Quality)
Consuming raw milk and milk-based products that have not been produced under strict control conditions can cause brucellosis, a highly contagious zoonotic disease. It is a significant global public health concern, particularly in regions with poor management and limited resources, such as Latin America, North and East Africa, the Middle East, and South and Central Asia. The study aims to summarize the occurrence of human brucellosis linked to milk and milk products and the presence of Brucella species in dairy foods. To achieve this goal, a meta-analysis was conducted on 69 studies ranging from 2001 to 2022, which were categorized into two groups: the incidence of Brucella species in milk and milk products and the prevalence of human brucellosis resulting from the consumption of contaminated milk. The following milk and milk products showed the highest incidence of Brucella species: cow milk (1.86%–81.7%), buffalo milk (10.4%–61.67%), camel milk (0%–24%), goat milk (0%–88.8%), and cheese (0%–39.1%). Consuming unpasteurized milk and milk products has been identified as the leading cause of human brucellosis, with incidence rates varying from 33.9% to 100%. Several human brucellosis cases have been linked to consuming raw milk and cheese in Spain, Israel, and other countries. Various serological techniques are employed to detect Brucella-specific antibodies in milk. The milk ring test (MRT) and enzyme-linked immunoassay (ELISA) are the two most widely utilized methods for detecting these antibodies in milk. Recently developed dual biosensors are a powerful approach for early diagnosis of Brucella from milk. Real-time PCR can rapidly detect organisms, reducing the risk of lab contamination and false positive results. To prevent and control brucellosis, essential steps include proper pasteurization of milk and dairy products, using the milk ring test (MRT) to detect Brucella in individual and bulk milk, immunization, education, and increasing public awareness of the disease. The consumption of raw milk and milk-made products that are not produced under strictly controlled conditions poses a significant risk to human health, mainly due to the high incidence of Brucella contamination. Therefore, ensuring strict control measures in producing milk and milk-made products is crucial to preventing the spread of this disease and safeguarding human health.